Assembly of nitrogenase biosynthetic pathway in Saccharomyces cerevisiae by using polyprotein strategy - Wang, Minyang; Shang, Yimin; Liu, Xiaomeng; Chen, Sanfeng (Frontiers in Microbiology, 2023)
Nitrogenase in some bacteria and archaea catalyzes conversion of N2 to ammonia. To reconstitute a nitrogenase biosynthetic pathway in a eukaryotic host is still a challenge, since synthesis of nitrogenase requires a large number of nif (nitrogen fixation) genes. Viral 2A peptide mediated “cleavage” of polyprotein is one of strategies for multigene co-expression. Here, we show that cleavage efficiency of NifB-2A-NifH polyprotein linked by four different 2A peptides (P2A, T2A, E2A and F2A) in Saccharomyces cerevisiae ranges from ~50% to ~90%. The presence of a 2A tail in NifB, NifH and NifD does not affect their activity. Western blotting shows that 9 Nif proteins (NifB, NifH, NifD, NifK, NifE, NifN, NifX, HesA and NifV) from Paenibacillus polymyxa that are fused into two polyproteins via 2A peptides are co-expressed in S. cerevisiae. Expressed NifH from Klebsiella oxytoca NifU and NifS and P. polymyxa NifH fusion linked via 2A in S. cerevisiae exhibits Fe protein activity.